Mixed‐Methods Evaluation of a Healthy Exercise, Eating, and Lifestyle Program for Primary Schools. (11th October 2017) - Cochrane, Thomas; Davey, Rachel C.
ABSTRACT: BACKGROUND: Reversing decline in physical fitness and increase in excess body weight in school children are considered major public health challenges. We evaluated a proposed model to integrate a screening and healthy exercise, eating, and lifestyle program (HEELP) into primary schools in Canberra, Australia. Objectives were: (1) to establish body status and physical competencies of 5‐ to 10‐year‐old children; (2) to evaluate the service's impact on body status and physical fitness; and (3) to gauge parent/guardian and school perspectives on the service. METHODS: A mixed‐methods approach was used over 4 school years, 2010‐2013. Primary evaluation used direct quantitative measurement. Confirmatory qualitative methods were implemented in the last 2 years. RESULTS: The service was delivered on 71 occasions involving 25 schools; 7750 children were screened and 709 completed all aspects of the HEELP evaluation. Over 60% of children screened had 2 or more measures that would benefit from remedial intervention. CONCLUSIONS: All body status and physical fitness measures showed small beneficial changes on a population basis immediately after the HEELP. Further benefit did not accrue at 6 months after the program. Semistructured interviews with schools and parent/guardian surveys confirmed some beneficial effects observed by direct quantitative measurement.